Implementasi Mikrotik-API Pada Filter rule Mikrotik OS Menggunakan PHP Native Untuk UPT Lab Universitas Amikom Yogyakarta - Muhammad Firdaus Ilhamy; Slameto, Andika Agus (LPPM Universitas Dinamika Bangsa, 2024)
Mikrotik Routeros is a popular network operating System used by network administrators. Equipped with a Firewall feature, managing Filter rules in controlling network access is important. However, the WEB interface or CLI can be difficult and time-consuming. One management alternative is to use the Mikrotik API which allows access through integrated programs or applications. Winbox is a common GUI application for controlling network access, but it has some problems. Users may cause accidental errors, and this app is only available for Windows, not for Mac os or Linux. Other alternatives such as CLI and API can be accessed from various platforms. At Amikom University, Yogyakarta, problems arOSe at the UPT (Technical Implementation Unit) Lab because they were still using Winbox to manage network permissions, especially on Filter rules. Therefore, this research project aims to reduce user errors by using the Mikrotik API. The use of this API enables more efficient and effective management of Filter rules through programs or applications as needed, increasing overall network security.